Survey Penerapan Kurikulum 2013 Pada Mata Pelajaran Penjas Di Sekolah Menengah Pertama Negeri : (Survey on the Implementation of the 2013 Curriculum in Physical Education Subjects at Public Middle Schools) - GioFani Pangaribuan Pangaribuan; Rifqi Aufan (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2020)
This study aims to determine the extent of the application of the 2013 curriculum in Physical Education subjects in the State Junior High Schools in Medan Tembung District. This research was conducted in Medan Tembung Subdistrict in 2019. The population in this study was the Public Middle School Physical Education Teacher in Medan Tembung Subdistrict. The sample in this study is total sampling which is the same as the population that is the Public Middle School Physical Education teacher in the District of Medan Tembung. Data collection techniques used are using survey techniques. Data were analyzed using quantitative descriptive analysis techniques. The results of this study indicate that: the average percentage of curriculum application in the State Junior High Schools in Medan Tembung District, for SMP Negeri 27 in the